Just sustainabilities and local action: evidence from 400 flagship initiatives. Issue 5 (4th May 2017) - Castán Broto, Vanesa; Westman, Linda
ABSTRACT: Just sustainabilities has emerged as a powerful discourse to guide local action towards sustainability. As an overarching discourse, it prescribes four policy principles: (1) addressing well-being and quality of life; (2) meeting the needs of present and future generations; (3) enabling justice and equity in terms of recognition, process, procedure, and outcome; and (4) living within ecosystem limits. Following previous calls for engaging public and private actors in just sustainabilities, this paper inquiries about the extent to which these principles can be realistically integrated in local environmental governance. A database of 400 sustainability initiatives in more than 200 cities in all world regions is analysed to examine whether just sustainabilities principles are already enshrined, explicitly or implicitly, in local sustainability initiatives. This analysis suggests that, in this sample, there is a significant deficit in terms of addressing the principles of justice and equity, and ecosystem limits. However, the data also suggest that local action may already be delivering some aspects of just sustainabilities, even if this is not always explicit. The paper concludes with a call for a coordinated effort to translate a just sustainabilities discourse to local actors leading action on the ground.